EU Regulations: Tendencies in Translating Lexical Bundles from English into Lithuanian - Noreika, Mantas; Šeškauskienė, Inesa (Vertimo studijos, 2017)
[full article, abstract in English; abstract in Lithuanian] Based on the theoretical framework of lexical bundle research developed by Biber et al. (2004) and on Sinclair’s (1991) observations on the compositionality of meaning and delexicalisation of formulaic language, the present study analyses four-word lexical bundles found in English EU legal discourse, focusing on their structural and semantic properties and tendencies of their translation into Lithuanian. The study examines a selection of 43 lexical bundles with a total of 791 unique instances in the corpus, extracted from a self-designed 59,579-word corpus representing EU legal English comprised of five regulations on health claims and food labelling. The results show that lexical bundles can be rendered into Lithuanian as single lexical or function words, phrases, dependent clauses, through the grammatical category of case, or omitted altogether. The length of the translated bundles suggests that there is a tendency to choose a shorter way of rendering them into Lithuanian. High variability of the translations of some lexical bundles points to a lack of their stability in Lithuanian, which might be due to a number of reasons, including a lack of agreement among translators and a much shorter tradition of legal translation into Lithuanian.